How do some primary schools in England organise and implement the broader curriculum?. Issue 4 (18th May 2020) - Pratt, Kip; Atkinson, Ruth
ABSTRACT: We are concerned by evidence of 'curriculum narrowing' in English primary schools. Inspection reports shed little light on the current situation, so we conducted a small qualitative study exploring breadth of curriculum provision. Eight teacher interviewees described eight different ways of organising and implementing the curriculum. While English and mathematics dominated many conversations, everyone expressed the importance of a broader curriculum and in some schools an engaging and genuinely broad curriculum is apparently alive and well. Assumptions about how best to teach English and mathematics may be one factor affecting curriculum breadth: in-depth case studies are suggested to examine this.